Förbättringsarbete och avvikelsehantering för ökad tjänstekvalitet hos SCA Skog AB Jämtlands skogsförvaltning - Andersson, Maria (SLU/Dept. of Forest Resource Management, 2009)

(untitled)
On a highly competitive market, quality is an important aspect to take into account, both in terms of goods and services. The Swedish timber market is very competitive and to achieve long-term success focus on the customer, in this case private forest owners, is a prerequisite.